(untitled) (Contemporary Central & East European Law, 2024)
The study demonstrates the actuality of the theses put forward by Stanisław Kasznica in the interwar period as regards the types of public law interference with the right to property. It is possible to make such an assessment, since immediately after Poland regained its independence the rule of law and the protection of private property were inscribed in its political foundations. Because Kasznica was aware of the fact that private property would be increasingly used in the public service, he made a graded classification of this interference on the basis of the regulations in force at the time. It turns out that his classification is also applicable in the Polish legal order in force.